PENAMBAHAN HAMBATAN DALAM PERHITUNGAN TAHANAN KAPAL AKIBAT GERAK KAPAL PADA GELOMBANG - Ariany, Zulfaidah (Diponegoro University, 2007)
Addition of resistance in calculation of ship resistance effect of ship motion at wave. Six natural degree offreedom by a ship thai is surging, swaying, heaving, rolling, pitching and yawing.In general movement bounce up ship have very complex geometry form and is influencing each other, eachother couple in an style system.Degradation of speed at ship done and conducted by at sea transport wayving (including wind) aim to avoidto damage or effect from green water on deck, slamming, racing propeller, and others. Is so that concludedthat calculation of ship resistance at ship progressively increase effect of ship motion at wave